ANALISIS SISTEM PENGENDALIAN INTERNAL DAN SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS (STUDI KASUS PADA SMART LEARNING CENTER DI PANGKALPINANG) - Feriyanti, Fiefie; Oktalina, Gayatria; Ahmad Agin, Arka’a (Jurnal Akuntansi Bisnis Dan Keuangan, 2019)
This undergraduate thesis was written and compiled by Fiefie Feriyanti (13014007), titled in Indonesian: "Analisis Sistem Pengendalian Internal Dan Sistem Informasi Akuntansi Penerimaan Kas (Studi Kasus Pada Smart Learning Center Di Pangkalpinang)". The purpose of this research is to find out whether the internal control system and accounting information system for cash receipts in the Smart Learning Center are adequate. This research is important to provide advice and recommendations on the Smart Learning Center about the system used. The theory used in this research is Accounting theory, Internal Control theory, Accounting Information System theory and Cash Receipt System theory. This type of research is a case study. The data used is obtained by observation, interviews and documentation. To achieve the objectives of the study, researchers conducted a comparison between the theory and practice carried out by the Smart Learning Center. The results of the study show that from the internal control system and inventory accounting information system that has been implemented by the Smart Learning Center, it is not relevant to be used in overcoming current obstacles. There are several indicators of problems that exist within the company, namely the multi-functional tasks and responsibilities of the Finance Sector which also act as Coordinators and Semi-Private Educators, submission of payments that can be made by Students through Administrative Staff and Staff - Educators, absence of accounting division to assist the Finance Department in recording and reporting cash receipts and lack of supervision from the leadership.